Expressão em superfície do sistema de falhas Poço Verde-caraúbas, Bacia Potiguar - Santos, Rafael Duarte (2011)
The structural knowledge of the western portion of the Potiguar Basin is still in its infancy, especially these related to NW-trending fault systems. This paper analyzes the Poço Verde-Caraúbas Fault System, which was initially recognized in subsurface. The activities involved in this study correspond to remote-sensing analysis and, in particular, to the geometric and kinematic analysis of post-rift sequences of the basin. In addition, the study aimed to determine the stress fields operating in the area. The studies were carried out in an area of 1,000 km², located in the western portion of Potiguar Basin along the Poço Verde-Caraúbas Fault System, Rio Grande do Norte State. The remote sensing imagery indicates a predominance of NW-SE-trending lineaments, consistent with the fault system under study, followed by the NE-SW, N-S and E-W directions. The tectonic structures mapped were analyzed only in outcrops of the Jandaíra Formantion. They are joints (filled or not) in all directions, but with predominance of the NW-trending joints. Faults are usually N-S-trending normal faults and NW-SE and NE-SW-trending strike-slip faults. Geodynamic analysis identified two tectonic stress fields: the first field, "Field 1" is represented by an N-S-trending horizontal compression and E-W-trending horizontal extension. This field affected the Potiguar Basin at least until the Miocene. The second field, "Field 2", is represented by an E-W-trending horizontal compression and N-S-trending horizontal extension. This is the present-day stress field and has affected the Potiguar basin since the Pliocene